An investigation of causal relationships among barriers that delay post-hurricane recovery of human communities - Rouhanizadeh, Behzad; Kermanshachi, Sharareh; Safapour, Elnaz (International journal of disaster risk reduction, 2022)
In the aftermath of hurricanes, the priority of decision makers is to return the affected community to its pre-disaster level of functioning. Recovery is a complex process, however, and is subject to several factors that might affect its timeliness. Therefore, understanding the barriers to timely post-hurricane recovery and determining the interrelations among them are highly important to planning for the recovery. This study investigates the causal relationships among the barriers that lead to delays in the process of recovery after hurricanes and determines the strength of those relationships. The barriers were identified by a thorough literature review, and the causal relationships were determined by implementing a social network analysis (SNA). The barriers that historically receive less attention in developing the mitigating frameworks and mathematical models were also identified. The results of this study show that misalignment among the policies, insufficient local government revenue, and lack of experience cause the most significant delays in recovery process; many other barriers, such as rate of employment, diversity of culture and languages, and damage to commercial buildings historically have not been adequately implemented in frameworks and models and deserve more consideration. The findings of this study will help the decision makers understand how the interactions of the barriers impact the timeliness of the recovery activities and will enable them to develop more reliable plans and frameworks for the recovery process.